Legal Protection for Children as Intermediaries in the Sale and Purchase of Narcotics - Gultom, Diana; Azhali Siregar, Mhd (PT. Multidisciplinary Press Indonesia, 2024)
The involvement of children in narcotics crimes as drug couriers is a series of evil conspiracy in carrying out illegal drug trafficking, but in the capacity of the category of children who help in trading or distribution by accompanying the owner of the goods with promises or enticements has often hit children of that age, this is a very concerning thing where the child has faced the law and is classified as having committed a drug crime. In this case, the child has committed an act, an evil conspiracy without rights or against the law offering for sale, selling, buying, receiving, being an intermediary in buying and selling, exchanging or handing over Class I Narcotics in the form of plants weighing more than 1 (one) kilogram or more than 5 (five) tree trunks or in the form of non-plants weighing more than 5 (five) grams. As a result of the action, the child as regulated and threatened with criminal penalties in Article 114 Paragraph (2) Jo Article 132 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics Jo Law Number 11 of 2012 concerning the Child Criminal Justice System. The type of research in writing this thesis is carried out with a type of normative legal research in the form of library research using 3 legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. This legal research focuses on library studies which means that it will examine and review more existing and applicable legal regulations. The results of this study indicate that Legal Protection for Children as Intermediaries in the Sale and Purchase of Narcotics in the Indonesian Legal System in Decision Number: 18/Pid.Sus-Anak/2023/PN.Bnj. namely by referring to Article 114 Paragraph (2) Jo Article 132 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics Jo Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, then the Child isMuhammad Pajar,proven legally and convincingly guilty of committing the crime of